Dissolving and biodegradable microneedle technologies for transdermal sustained delivery of drug and vaccine - Hong X; Wei L; Wu F; Wu Z; Chen L; Liu Z; Yuan W (Dove Medical Press, 2013)
Xiaoyun Hong,1,2,* Liangming Wei,3,* Fei Wu,2,* Zaozhan Wu,2 Lizhu Chen,2 Zhenguo Liu,1 Weien Yuan2 1Department of Neurology, Xinhua Hospital, Shanghai, People's Republic of China; 2School of Pharmacy, Shanghai JiaoTong University, Shanghai, People's Republic of China; 3Research Institute of Micro/Nano Science and Technology, Shanghai JiaoTong University, Shanghai, People's Republic of China *These authors contributed equally to this work Abstract: Microneedles were first conceptualized for drug delivery many decades ago, overcoming the shortages and preserving the advantages of hypodermic needle and conventional transdermal drug-delivery systems to some extent. Dissolving and biodegradable microneedle technologies have been used for transdermal sustained deliveries of different drugs and vaccines. This review describes microneedle geometry and the representative dissolving and biodegradable microneedle delivery methods via the skin, followed by the fabricating methods. Finally, this review puts forward some perspectives that require further investigation. Keywords: microneedle, dissolving, biodegradable, sustained release